Strategi Pelayanan Pendidikan Agama Kristen Remaja di Gereja Bethel Indonesia Jemaat Rajawali dengan Jumlah Remaja Terbatas - Ronald Evandi Aden (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study examines the strategy of Christian Religious Education (CRE) ministry for adolescents at Gereja Bethel Indonesia Rajawali Congregation, where the limited number of youth members presents unique challenges to ministry implementation. The study aims to identify the ministry strategies applied, the obstacles encountered, and the efforts made to overcome those obstacles in order to strengthen adolescents’ spiritual growth and participation in church activities. This research employs a qualitative descriptive approach. Data were collected through interviews, observations, and documentation, with information obtained from church leaders and youth ministry servants. The findings indicate that effective ministry strategies include building personal relationships with adolescents, conducting small-group sharing sessions, utilizing interactive learning methods, integrating digital media into ministry activities, and organizing contextual programs that correspond to the needs of young people. The study also reveals several challenges, including limited parental and church support, a small number of active adolescents, and the influence of digital culture on youth engagement. The implications of this research emphasize the importance of collaborative efforts among church leaders, parents, and youth mentors in developing creative, contextual, and sustainable ministry programs that encourage adolescents to grow spiritually and actively participate in the life and mission of the church.